Right Ventricular Adaptation in Congenital Heart Diseases - Beatrijs Bartelds (Journal of Cardiovascular Development and Disease, 2014)
In the last four decades, enormous progress has been made in the treatment of congenital heart diseases (CHD); most patients now survive into adulthood, albeit with residual lesions. As a consequence, the focus has shifted from initial treatment to long-term morbidity and mortality. An important predictor for long-term outcome is right ventricular (RV) dysfunction, but knowledge on the mechanisms of RV adaptation and dysfunction is still scarce. This review will summarize the main features of RV adaptation to CHD, focusing on recent knowledge obtained in experimental models of the most prevalent abnormal loading conditions, i.e., pressure load and volume load. Models of increased pressure load for the RV have shown a similar pattern of responses, i.e., increased contractility, RV dilatation and hypertrophy. Evidence is accumulating that RV failure in response to increased pressure load is marked by progressive diastolic dysfunction. The mechanisms of this progressive dysfunction are insufficiently known. The RV response to pressure load shares similarities with that of the LV, but also has specific features, e.g., capillary rarefaction, oxidative stress and inflammation. The contribution of these pathways to the development of failure needs further exploration. The RV adaptation to increased volume load is an understudied area, but becomes increasingly important in the growing groups of survivors of CHD, especially with tetralogy of Fallot. Recently developed animal models may add to the investigation of the mechanisms of RV adaptation and failure, leading to the development of new RV-specific therapies.